2018
DOI: 10.1177/0731121418782186
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Employment and Health in South Korea: The Role of Gender and Family Status

Abstract: Using nationally representative longitudinal data collected in South Korea from 2006 to 2013, this study evaluates the associations between nonstandard employment and various health outcomes with a focus on gender differences. We also examine to what extent family status, that is, marital status and parenthood, conditions these associations for men and women. Our results reveal an important role of selection in that many of the significantly negative associations between nonstandard/self-employment and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
3
8
1
Order By: Relevance
“…It is noteworthy that none of the variables included in the statistical model significantly predict self-rated health among Korean men, who could be considered a more prestigious group in the labor market. This finding echoes that of a previous study [ 13 ], which found no impact from self-employment or nonstandard employment on health outcomes among men in Korea; however, these types of employment negatively impact health among women. To explain this difference by gender, Lim and her colleagues [ 13 ] suggested that women are already negatively selected into these types of employment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is noteworthy that none of the variables included in the statistical model significantly predict self-rated health among Korean men, who could be considered a more prestigious group in the labor market. This finding echoes that of a previous study [ 13 ], which found no impact from self-employment or nonstandard employment on health outcomes among men in Korea; however, these types of employment negatively impact health among women. To explain this difference by gender, Lim and her colleagues [ 13 ] suggested that women are already negatively selected into these types of employment.…”
Section: Discussionsupporting
confidence: 88%
“…This finding echoes that of a previous study [ 13 ], which found no impact from self-employment or nonstandard employment on health outcomes among men in Korea; however, these types of employment negatively impact health among women. To explain this difference by gender, Lim and her colleagues [ 13 ] suggested that women are already negatively selected into these types of employment. Future studies must explore other factors related to the health of Korean immigrant men in the US.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…NSE includes various arrangements such as part-time jobs, fixed-contract work, on-call/day labor, and temporary-help agency work that differ from the standard, full-time employment relationship (Kalleberg et al, 2000) and are often characterized by low earnings, limited benefits, employment insecurity, and few opportunities for career advancement (Fuller, 2011;Giesecke & Groß, 2003;Kalleberg et al, 2000;McDonald et al, 2009;McGovern et al, 2004). The rapid growth in NSE represents a profound structural transformation in the labor market that has widespread social consequences for other nonwork domains of individuals and families (Kalleberg, 2018;Kalleberg & Vallas, 2017), such as health (Lim et al, 2018), homeownership (Lersch & Dewilde, 2015), marriage, and family formation (Lim, 2017;Piotrowski et al, 2015;. However, we know relatively little about relationships between nonstandard work arrangements and subjective well-being (SWB) and how they may vary across social categories, including gender.…”
Section: Introductionmentioning
confidence: 99%